Autoridad religiosa y autoridad política en "De haruspicum responso" de Cicerón - Cairo, María Emilia (2017)
The aim of this paper is to analyze the relationship between religious knowledge and belonging to the group of the boni cives, as formulated by Cicero in his speech De haruspicum responso. We argue that, both when he rejects Clodius? accusations and when he presents his own interpretation of the responsum, Cicero claims the correlation between knowledge of religio and political auctoritas. Then we turn to the definition of deteriores cives in order to observe how Cicero includes Clodius in this group, excluding him from the group of boni cives, because of his violation of every single religious norm and his conspi- ration against the harmony of the optimates. Finally, we present an analysis of the sources of religious authority and its connection to the Roman identity as presented in sections 18-19 of the speech